PHYSICAL EXERCISE IN THE MENSTRUAL CYCLE AND WOMEN’S HEALTH: REVIEW (Fiep Bulletin - online, 2024)
Introduction: During the Menstrual Cycle (CM) phase, it is common for changes to occur in a woman's disposition and body, manifesting themselves in different ways, which can generate negative implications during Strength Training (TF). Objective: To explore the relationship between TR in different phases of CM and present the implications for women's health. Methodology: This study was composed of a narrative literature review. The following platforms were used: PubMed, Scopus, MedLine, SciELO, Portal Periódicos CAPES and Virtual Health Library (VHL); where studies were selected only from 2019 to 2024. The descriptors were in Portuguese and English, using the Boolean operator “and” between the words. Results: The review consists of a narrative discussion of eight articles, with a total of 151 women with an average age of 26.04 years and a body mass of 60.53kg. The menstrual cycle can cause changes in women's physical performance, influencing muscle power and strength, resulting in greater fatigue. To achieve this, we suggest ingesting caffeine to aid performance, but above all, respect the Early Follicular phase. However, three articles found no changes in women's physical performance, revealing that the MC phase is not capable of affecting muscle strength levels. Conclusion: It is clear that the results are not yet consistent enough to provide support for women's health regarding RT and CM, making more research on the topic necessary.